Kara łączna po nowelizacji — rozważania na tle przepisów rozdziału IX Kodeksu karnego - Niewiadomska-Krawczyk, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article refers to the amendments introduced to regulations of Chapter IX of the Criminal Code which came into force on 1st July 2015The aim is to point out which of them are the most important in the process of imposition of aggregate penalty, how they create the new model of aggregate penalty as well as to consider whether they are reasonable.
Keywords: aggregate penalty; amendments; imposition of aggregate penalty; aggregate sentence; actual concurrence of crimes